Pengembangan Aplikasi Buku Penghubung Berbasis Web Sebagai Media Interaksi Sekolah – Orang Tua - Heri Kuswanto; Baiq Desi Dwi Arianti (Fakultas Teknik Universitas Hamzanwadi, 2022)
Communication book is one of supporting instrument of communication mechanism of teacher and parents considered not yet effective. Thus, it is necessary to develop a communication book in the digital environment as a solution to the problem. This study aims to develop communication book applications as a medium of communication between teachers and parents. This research uses research and development (R D) method with waterfall model approach that focused on efforts to produce a prototype of the product. Stages of research and development include communication, planning, modeling, construction, and deployment. Web-based development product using MVC design pattern concept with YII framework through the testing unit and ISO25010 standard quality. The result of this research and development is a prototype of communication book application as a proof of concept towards the approach used.